An Analysis of Decision-Making, Nature, and Emotions in Robert Frost’s ’The Road Not Taken’ and William Wordsworth’s ’I Wandered Lonely as a Cloud’ Through Relevance Theory" (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper examines Robert Frost’s "The Road Not Taken" and William Wordsworth’s "I Wandered Lonely as a Cloud," using relevance theory to assess how the poems enhance their relevance for readers. The aim is to examine how the poems use communication techniques that fit the context, create inferences, and improve meaning. Using Relevance Theory as a foundation, the study delves into themes like choices, nature, emotion, solitude, and connection portrayed in the works. This research employs qualitative methods to evaluate how Frost and Wordsworth convey meaning effectively, sparking interpretations from readers. This research aims to enhance understanding of how poets use language and imagery to connect with readers, emphasizing personal choices, nature’s impact on emotions, and the interplay between solitude and connection in poetry. The findings indicate that poets frequently use their personal experiences and feelings to craft works that deeply resonate with readers.